Altered Cortical Reorganization and Brain Functional Connectivity in Phantom Limb Pain: A Functional MRI Study. Issue 4 (6th December 2020) - Zheng, Bi‐Xin; Yin, Yan; Xiao, Hong; Lui, Su; Wen, Chuan‐Bing; Dai, Yue‐E; Yang, Guang; Liu, Jin; Gong, Qiyong
Abstract: Objectives: Functional neuroimaging studies have shown that amputees have altered cortical reorganization and functional connectivity (FC). This study aimed to investigate whether patients with phantom limb pain (PLP) and PLP‐free lower limb amputees exhibit changes in corresponding primary cortical motor area/somatosensory cortex (M1/S1) cortical reorganization and supplementary motor area (SMA) network FC. The association between functional magnetic resonance imaging (fMRI) changes and clinical parameters is also explored. Methods: A total of 10 PLP patients were matched with 10 PLP‐free amputees and 10 healthy controls (HCs). Before undergoing fMRI, all participants completed questionnaires evaluating pain, anxiety, depression, and health‐related quality of life. Task‐related activation and regions of interest (ROI)‐wise connectivity analysis were applied to differentiate the brain regions of amputees from those of HCs. Linear correlation analysis was used to evaluate the correlation between altered FC and clinical manifestations. Results: As compared with HCs, PLP patients showed increased cortical activation in M1/S1 when moving the intact foot, imagining phantom big toe movement, or having the corresponding thumb stimulated. The increased FC in the SMA network included the SMA‐caudate nucleus, SMA‐bilateral insula, and SMA‐anterior cingulate cortex. Furthermore, results of the linear correlation analysis demonstrated that this increased FC was positively correlated with VAS scores, negatively correlated with Medical Outcomes Study 36‐item Short‐Form (SF‐36) scores, and not correlated with anxiety or depression scores. Conclusions: Phantom limb pain in lower limb amputees is associated with M1/S1 cortical reorganization and altered SMA network FC in different areas of the brain, which could help to support our understanding of the central mechanism of PLP.